2018
DOI: 10.1590/1808-057x201804890
|View full text |Cite
|
Sign up to set email alerts
|

To pursue a career in accounting or not: a study based on the Theory of Planned Behavior

Abstract: ABSTRACTis study investigates the intention of 691 students graduating from Accounting courses at public universities in the state of Paraná to pursue a career in the area of accounting, based on the eory of Planned Behavior. For the analysis, the sample was divided into ten mesoregions according to the criteria of the Paranaense Institute for Economic and Social Development (Ipardes). e data collected were treated using descriptive statistics and structural equations techniques. e research hypotheses were cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
5
0
4
Order By: Relevance
“…The results of hypothesis testing are supported by several previous studies (Wen, Yang, Bu, Diers, & Wang, 2018;Bekoe et al, 2018;Dos Santos & De Almeida, 2018). They found that accounting students' decision to choose an accounting career was significantly influenced by their attitudes toward the profession of accounting.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The results of hypothesis testing are supported by several previous studies (Wen, Yang, Bu, Diers, & Wang, 2018;Bekoe et al, 2018;Dos Santos & De Almeida, 2018). They found that accounting students' decision to choose an accounting career was significantly influenced by their attitudes toward the profession of accounting.…”
Section: Resultssupporting
confidence: 78%
“…Several previous studies by Mbawuni (2015); Bekoe et al (2018), and Dalcı and Özyapıcı (2018) found that perception was able to affect someone's career choices. Santos and Almeida (2018) agreed that the perception of accounting students on the accountant, or accounting work, was important in influencing selfimage, belief, and attitude towards the accounting profession.…”
Section: Introductionmentioning
confidence: 92%
“…Hal tersebut menunjukkan bahwa seseorang akan berminat mengikuti PPAk apabila memiliki sikap positif bahwa mengikut i PPAk merupakan kegiatan yang membawa keuntungan bagi seseorang tersebut, sebaliknya minat seseorang akan rendah apabila seseorang bersikap negatif yaitu beranggapan bahwa mengikuti PPAk akan memberikan kerugian bagi seseorang tersebut. Beberapa penelitian yang telah dilakukan oleh Yuniarti (2016), Vesperalis & Muliartha (2017), Dewi & Budiasih (2017), Dewi & Ratnadi (2018) , Dos Santos & De Almeida (2018), Wen et al (2018), Wijaya (2020) menemukan bahwa semakin besar keyakinan seseorang bahwa mengikuti PPAk mendatangkan konsekuensi yang positif maka semakin tinggi minat mahasiswa untuk mengikuti PPAk. Berdasarkan pemaparan teoritis dan hasil penelitian yang dilakukan sebelumnya, maka dihipotesiskan sebagai berikut.…”
Section: Pendahuluanunclassified
“…Several studies have made use of several models and theories to explain accounting students" career intentions. These theories include the Theory of Reasoned Action (TRA) (Law, 2010), Theory of Planned Behaviour (TPB) (Srirejeki et al, 2019;Santos, 2018;Amani and Mkumbo, 2016;Mbawuni and Nimako, 2015;and Social Cognitive Theory (SCT) (Bello (2019). This study adopts the TPB as a fundamental theory.…”
Section: Theoretical Frameworkmentioning
confidence: 99%